2016
DOI: 10.7759/cureus.604
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Virulence Factors and Antibiotic Sensitivity Pattern of Escherichia Coli Isolated from Extraintestinal Infections

Abstract: Introduction Identification of virulence determinants among the clinically isolated microorganisms assumes greater significance in the patient management perspective. Among the hospitalized patients, extremes of age groups (neonatal and geriatric age patients), patients who are debilitated due to other associated medical conditions, patients taking immunosuppressive therapy, and patients undergoing major surgeries are prone to infections with previously nonpathogenic or opportunistic pathogens. Screening of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Previous studies have shown that urinary and peritoneal isolates are most hydrophobic [22] suggesting relation of hydrophobicity with pathogenicity. [42,43,14]. Occurrence of lower numbers of virulence factors from healthy individuals compared with diarrheic children is in consistence with other workers who found lower prevalence of virulence factors in commensal E. coli [42].…”
Section: Antibiotic Susceptibility Findingssupporting
confidence: 55%
See 1 more Smart Citation
“…Previous studies have shown that urinary and peritoneal isolates are most hydrophobic [22] suggesting relation of hydrophobicity with pathogenicity. [42,43,14]. Occurrence of lower numbers of virulence factors from healthy individuals compared with diarrheic children is in consistence with other workers who found lower prevalence of virulence factors in commensal E. coli [42].…”
Section: Antibiotic Susceptibility Findingssupporting
confidence: 55%
“…[42,43,14]. Occurrence of lower numbers of virulence factors from healthy individuals compared with diarrheic children is in consistence with other workers who found lower prevalence of virulence factors in commensal E. coli [42]. Moreover occurrence of multivirulence factors in fish isolates cautions that fish could be potential source of pathogenic E coli.…”
Section: Antibiotic Susceptibility Findingsmentioning
confidence: 68%
“…An important microbial characteristic associated with virulent avian E . coli is a hemolytic reaction on blood agar plates 14 , 15 – hemolytic strains are more virulent than non-hemolytic strains 16 , 17 . α-Hemolysin, also known as cytotoxic necrotizing factor, is produced by invasive strains of E .…”
Section: Discussionmentioning
confidence: 99%
“…Results of the serological identification showed 14 serotypes of E. coli as shown in Table (2). The isolated E. coli serotypes are O8, O20, O27, O44, O78, O114, O125, O142, O146, O152, O153, O158, O164, O166, and O Untypable.…”
Section: Serological Identification Of E Colimentioning
confidence: 99%
“…Escherichia coli (E. coli), is harmless, normal inhabitants of the gastrointestinal tract of animals and human beings [1]. Specific strains of E. coli can invade multiple birds' organs, causing peritonitis, perihepatitis, air sacculitis, pericarditis and other extraintestinal infections [2]. Avian colibacillosis is the most common disease leading to significant economic losses to the poultry industry in the world [3].…”
Section: Introductionmentioning
confidence: 99%